2017
DOI: 10.1371/journal.pone.0175703
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognoses of patients with ovarian cancer using bevacizumab: 6-year experience in a tertiary care hospital of northern Taiwan

Abstract: PurposeBevacizumab (BEV) has been used for ovarian cancer (OC) for years in Taiwan, but the associated data related to outcome is scant. This retrospective study reviewed patients with OC treated with BEV and analyzed their results.Patients and methodsAll patients with OC treated with BEV from 2009 to 2015 in the Linkou branch of Chang Gung Memorial Hospital in Northern Taiwan were included. According to the means of administration, the patients were classified into 6 groups as follows: A—BEV plus chemotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…However, direct causality is still not proven between them and OC (Tsilidis et al, 2011). Various factors, including atypical clinical symptoms, insufficient early detection modalities, late-onset diagnosis, chemoresistance, recurrence, and metastatic spread, lead to high mortality of ovarian cancer (Burges and Schmalfeldt, 2011;Chen et al, 2017;Klapdor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, direct causality is still not proven between them and OC (Tsilidis et al, 2011). Various factors, including atypical clinical symptoms, insufficient early detection modalities, late-onset diagnosis, chemoresistance, recurrence, and metastatic spread, lead to high mortality of ovarian cancer (Burges and Schmalfeldt, 2011;Chen et al, 2017;Klapdor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While constituting only 3% of the cancer cases affecting women, ovarian cancer is a fatal malady due to its unpredictable prognosis, poor refractory outcome, onco-therapeutic resistance, metastatic spread and ultimate relapse with no signs of improvement in patient survival to date [ 1 ]. In recent years, existence of various cancer stem cells (CSCs) in ovarian tumor, as well as in ascites from patients with ovarian cancer have been reported as a cause of tumor relapse and recurrence, thus imposing a clinical problem [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a Phase III trial, IP cisplatin (40 mg/m 2 ) plus bevacizumab (300 mg), every 2 weeks for 6 weeks, was superior to the same dose of IP cisplatin alone (ORR 90.32 vs. 59.26%, p < 0.05), and resulted in significantly reduced VEGF and CA-125 levels in ascites fluid [35]. Early data suggestive of a role for IP bevacizumab in the palliation of malignant ascites in recurrent ovarian cancer [36,37] are supported by clinical experience demonstrating improved ascites with IP-administered bevacizumab (5 mg/kg) in 6/7 (85.6%) patients [38]. The Phase II REZOLVE study has demonstrated that IP bevacizumab (5 mg/kg), administered following paracentesis, increased the median time of paracentesis-free intervals by 4.3-fold compared to the time between paracenteses before entry into the study [39].…”
Section: Discussionmentioning
confidence: 90%